EXTRACELLULAR VESICLES: CLASSIFICATION, FUNCTIONS AND CLINICAL RELEVANCE - A. V. Oberemko; A. G. Popandopulo (Biotechnologia Acta, 2014)
This review presents a generalized definition of vesicles as bilayer extracellular organelles of all celular forms of life: not only eu-, but also prokaryotic. The structure and composition of extracellular vesicles, history of research, nomenclature, their impact on life processes in health and disease are discussed. Moreover, vesicles may be useful as clinical instruments for biomarkers, and they are promising as biotechnological drug. However, many questions in this area are still unresolved and need to be addressed in the future.